The EEG Photoparoxysmal Response - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Types of photosensitivity, prevalence and other characteristics of the photoparoxysmal response (PPR), associated seizures, effect of video games, and drug therapy are reviewed by the director of electroencephalography at the University of Illinois, Chicago.